Mechanical integrity of nano-interconnects as brittle-matrix nano-composites. (June 2018) - Zahedmanesh, Houman; Vanstreels, Kris; Toan Le, Quoc; Verdonck, Patrick; Gonzalez, Mario
Highlights: Delamination of advanced nano-interconnects under external stresses was deciphered. A consolidated framework for efficient analysis of their mechanical integrity was introduced. The impacts of key design parameters on the mechanical integrity were investigated and design guidelines were provided. Abstract: In this study, the mechanical integrity of advanced multilayer nano-interconnects, as metal/dielectric nano-composites, was investigated using a combination of analytical modelling, computational mechanics and experiments. A method for fast derivation of the effective orthotropic elastic moduli of complex multilayer nano-interconnects was demonstrated and corroborated using finite element modelling (FEM). Subsequently, the effective elastic properties were employed for homogenization and course-graining in computational fracture mechanics models. This allowed the model development and simulation time to be reduced drastically and also enabled the global delamination behavior in nano-interconnects to be predicted consistent with experimental results. The study identified the via layers integrated with ultra low-k (ULK) dielectrics as the delamination prone layers. Particularly, failure analysis following exposure to bump shear tests revealed that the via layer adjacent to the top stiff layers was the dominant fracture path. By using analytical and computational mechanics it is shown that the elasticity mismatch between the soft intermediate group of layers and the stiff top group of layers dictates this delamination mode. Detailed FE modeling, showed that when vias are uniformly distributed, increasing the via density by only a few percent will increase the mechanical integrity drastically. Delamination experiments revealed a statistically significant increase of critical fracture energy (Gc ) of ULK dielectric films when their thickness is reduced. Thus, reducing the thickness of the via layers, will also increase their effective Gc . However, analytical modelling together with experiments indicate that this trend will apply down to an optimal via layer thickness of approximately 30 nm where the Gc is predicted to reach its theoretical maximum in the case of organosilicate glass ULK (OSG 2.55).